2001
DOI: 10.1007/s10227-001-0005-1
|View full text |Cite
|
Sign up to set email alerts
|

Betamethasone Valerate in Foam Vehicle Is Effective with Both Daily and Twice a Day Dosing: A Single-Blind, Open-Label Study in the Treatment of Scalp Psoriasis

Abstract: BMV foam is effective for scalp psoriasis with both once-a-day and twice-a-day use. This feature of the BMV foam is encouraging for expected improvement in clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 4 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…Eighteen trials focused on the use of topical steroids for scalp psoriasis 53–56,58–71 . Sixteen were between‐patient 53–56,58–66,68–70 and two were within‐patient studies 67,71 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eighteen trials focused on the use of topical steroids for scalp psoriasis 53–56,58–71 . Sixteen were between‐patient 53–56,58–66,68–70 and two were within‐patient studies 67,71 .…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen trials focused on the use of topical steroids for scalp psoriasis 53–56,58–71 . Sixteen were between‐patient 53–56,58–66,68–70 and two were within‐patient studies 67,71 . Treatment duration ranged from 2 to 8 weeks with the majority of durations being less than 6 weeks 27,53–56,59–63,66–69,71 The number of enrolled patients varied from 42 to 1417 patients according to the trial (mean 395 patients).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 32 Another trial on 79 patients showed that once daily application of BMV 0.12% foam was as effective as twice daily application for 4 weeks. 33 This is important given that once daily efficacious treatment has a much higher adherence rate as compared to twice daily treatments. 34 …”
Section: Treatment Of Scalp Psoriasismentioning
confidence: 99%